التراث اللامادي حمايته وتثمينه، وأبعاده المستدامة - KHABZAOUI, Abdelkarim (My University, 2017)
The social and moral systems, customs, traditions and arts at the different Arabic and oriental peoples, are a living memory which doesn't perish with time changes, not either with place changes, for being an important part of human history, and evolution of remaining and continuing civilizations, therefore they are considered as part of the human heritage, and they became incumbent for everyone to make protection procedures and ensure the sustainability using various ways and means, and exploit them durably. We will treat these dimensions in this study to protect and valorize non-material heritage with durable dimension.
Patrimoine immatériel : sa protection, sa valorisation et ses dimensions durables